2017
DOI: 10.3390/polym9070264
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Polymer Grafting from a Graphene Oxide Surface on Its Compatibility with a PDMS Matrix and the Light-Induced Actuation of the Composites

Abstract: Poly(dimethyl siloxane) (PDMS)-based materials with improved photoactuation properties were prepared by the incorporation of polymer-grafted graphene oxide particles. The modification of the graphene oxide (GO) surface was achieved via a surface initiated atom transfer radical polymerization (SI ATRP) of methyl methacrylate and butyl methacrylate. The modification was confirmed by thermogravimetric analysis, infrared spectroscopy and electron microscopy. The GO surface reduction during the SI ATRP was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…DMA was also conducted to study the mechanical properties of composite materials. Through this investigation, the storage modulus and the transition of crystallization melting of composites were observed. As presented in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…DMA was also conducted to study the mechanical properties of composite materials. Through this investigation, the storage modulus and the transition of crystallization melting of composites were observed. As presented in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Graphene-based particles have been determined to be better candidates due to their two-dimensional shape, as well as large surface area [25]. Graphene particles are of particular interest since they provide high electrical conductivity, excellent mechanical properties and high thermal conductivity, that facilitate heat transfer within the sample [26], and can also improve the photo-actuation capability [27]. However, the dispersion and distribution of neat graphene nanoparticles in a polymer is rather problematic due to the strong π-π interaction between the graphene sheets [28].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the studies of poly(dimethyl silioxane) (PDMS) filled with graphene oxide polymer hybrids (GO-g-polymer) photo-actuators also revealed that through surfaced modification we were able to improve the affinity GO-g-polymer particles to a PDMS matrix. SI-ATRP enables one to finely tune the properties of the chemical cross-linking network in terms of decreasing the activation energy of glass transition (systems possess enhanced flexibility of the PDMS network) that finally improves the ability for photo-actuation [21,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Smart systems belong to the group of materials capable of changing the basic properties, when they are exposed to external stimuli such as electric [1][2][3], magnetic [4,5], thermal [6,7], pH [8,9], or light [10,11]. In case of light stimulation, such smart systems can exhibit the shape [12] or resistivity [13] change or generate electric output [14].…”
Section: Introductionmentioning
confidence: 99%